The Policy of PT Len As a Main Integrator on Increasing National Income - Juliana, Juliana; Saputro, Guntur Eko (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
PT Len's defense industry policy, in collaboration with Thales, is focused on the development of the national radar industry. The cooperation demonstrates the domestic industry's inability to support the defense industry's independence. The research goal is to give advice to PT LEN on military industry implementation and strategy. The goal of qualitative research is to comprehend phenomena from the perspective of the participants. The results showed that the outcomes are consistent with the implementation theory in terms of communication, resources, personnel, budget, and disposition. To anticipate delays in the revitalization process for the defense industry that is not ready to carry out technology transfer, the strategy requires adequate resources, supporting facilities, and infrastructure, as well as an inventory of national companies engaged in the industrial defense sector.